Relativismo lingüístico, relativismo ontológico - Alberto Escalera Narváez (Nóesis)
This article presents and explores some of the fundamental ideas related to the so-called linguistic (or deterministic) relativism. Linguistic relativism is represented in the contemporary era by the so-called Sapir- Whorf Hypothesis. This states that there is a systematic connection between the grammatical categories of a language and the way its speakers conceive, categorize or interpret the world. What this connection may consist of and to what extent it takes place is, obviously, a matter of controversy. In addition to presenting some ideas in favor and others against this hypothesis, I will argue, in the conclusion of this article, that it is necessary to take into account not only the empirical-linguistic aspect, but also the ontological-philosophical one of this hypothesis for a better understanding of this problem.